MINI SOLAR PANEL PROPS WITH GUIDED INQUIRY MODEL TO IMPROVE SCIENCE LITERACY - Andini Pertiwi; Maryati Maryati; Sarina Sarina; Jumadi Jumadi; Insih Wilujeng; Laifa Rahmawati (Jurnal Eduscience)
Purpose – This research aims to find out:  (1) the effectiveness of using mini solar panel props with guided inquiry models to improve students' science literacy, (2) whether there is a difference in the average score of significant improvement in students' science literacy before and after the implementation of mini solar panel props with guided inquiry models, (3) how much the effect size of using mini solar panel props with guided inquiry models to improve students' science literacy.